Diffuse fatal infantile hemangioendothelioma in an infant liver: Case report - Serkan Şenol (Journal of Clinical and Experimental Investigations, 2015)
Infantile hemangioendothelioma is a rare tumor in the liver in children under 3 years of age. It is usually incidentally detected but may also occur with liver enlargement. Herein a case of neonatal infantile hemangioendothelioma in liver with hepatosplenomegaly and respiratory-circulatory failure resulting in monitoring is presented with literature. J Clin Exp Invest 2015; 6 (3): 312-314